2016
DOI: 10.12957/jse.2016.23096
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Particulate Organic Matter in Holocene Sediments of Coastal Plain From Pero Beach, Cabo Frio, Rio De Janeiro, Brazil

Abstract: The study of palynofacies along a core drilled on the coastal plain of Cabo Frio, State of Rio de Janeiro, was carried out in order to contribute to the knowledge of the paleoenvironmental evolution of the Pero Beach region. The ages obtained from 14 C datings allowed to verify that the studied core records the past 6761 ± 130 yrs cal BP. Thirty samples were prepared by standard methodology for palynofacies. About three hundred particles of the particulate organic material was classified and recorded for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…KUHN et al Several palynological studies in Southern and southeastern Brazil based on palynomorph analysis have demonstrated the coastal environmental changes in response to Holocene sea-level variation (de Oliveira et al 2005). However, little is known about the paleoenvironmental history of Santa Catarina Coastal Plain (e.g., Slompo 1997, Behling and Negrelle 2001, Amaral et al 2012, when compared to nearby areas, especially Rio Grande do Sul (see summary in Bauermann et al 2009) and Rio de Janeiro States (e.g., Luz et al 2006, Freitas and Carvalho 2012, Souza et al 2016.…”
mentioning
confidence: 99%
“…KUHN et al Several palynological studies in Southern and southeastern Brazil based on palynomorph analysis have demonstrated the coastal environmental changes in response to Holocene sea-level variation (de Oliveira et al 2005). However, little is known about the paleoenvironmental history of Santa Catarina Coastal Plain (e.g., Slompo 1997, Behling and Negrelle 2001, Amaral et al 2012, when compared to nearby areas, especially Rio Grande do Sul (see summary in Bauermann et al 2009) and Rio de Janeiro States (e.g., Luz et al 2006, Freitas and Carvalho 2012, Souza et al 2016.…”
mentioning
confidence: 99%
“…(), McGowen & Scott (), Swift () or McCubbin (), is proposed as the most plausible scenario. Moreover, the very low proportion of marine‐derived palynomorphs and the significant contribution of the miospore content are also indicative of restricted, low‐energy lagoonal environments (Pieñkowski & Waksmundzka, ; Souza et al ., ).…”
Section: Facies Associationsmentioning
confidence: 65%
“…Since the occurrence of marine algae precludes a purely terrestrial environment, a restricted low-energy lagoonal setting with swamped deposits, such as that defined by Davies et al (1971), McGowen & Scott (1975), Swift (1975) or McCubbin (1982), is proposed as the most plausible scenario. Moreover, the very low proportion of marine-derived palynomorphs and the significant contribution of the miospore content are also indicative of restricted, lowenergy lagoonal environments (Pieñkowski & Waksmundzka, 2009;Souza et al, 2016). At the lagoonal rim, storm episodes rich in marine particles arrived as weak bottom currents.…”
Section: Discussionmentioning
confidence: 99%
“…According to Souza et al (2016), the study of the organic matter present in sediments of coastal and marine areas has been widely used in the reconstruction of environmental evolution in different regions of Brazil. For Ramirez et al (2018), marginal basins play an important role in understanding depositional processes such as those involved in the opening of the Atlantic Ocean when South America i i i separated from Africa.…”
Section: Introductionmentioning
confidence: 99%